A stripped helium star in the potential black hole binary LB-1 - Irrgang, Andreas; Geier, Stephan; Kreuzer, Simon; Pelisoli, Ingrid; Heber, Ulrich (Astronomy & Astrophysics, 2020)
Context. The recently claimed discovery of a massive (M-BH = 68(-13)(+11) M-circle dot) black hole in the Galactic solar neighborhood has led to controversial discussions because it severely challenges our current view of stellar evolution.Aims. A crucial aspect for the determination of the mass of the unseen black hole is the precise nature of its visible companion, the B-type star LSV +22 25. Because stars of different mass can exhibit B-type spectra during the course of their evolution, it is essential to obtain a comprehensive picture of the star to unravel its nature and, thus, its mass.Methods. To this end, we study the spectral energy distribution of LSV +22 25 and perform a quantitative spectroscopic analysis that includes the determination of chemical abundances for He, C, N, O, Ne, Mg, Al, Si, S, Ar, and Fe.Results. Our analysis clearly shows that LSV +22 25 is not an ordinary main sequence B-type star. The derived abundance pattern exhibits heavy imprints of the CNO bi-cycle of hydrogen burning, that is, He and N are strongly enriched at the expense of C and O. Moreover, the elements Mg, Al, Si, S, Ar, and Fe are systematically underabundant when compared to normal main-sequence B-type stars. We suggest that LSV +22 25 is a stripped helium star and discuss two possible formation scenarios. Combining our photometric and spectroscopic results with the Gaia parallax, we infer a stellar mass of 1.1 +/- 0.5 M-circle dot. Based on the binary system's mass function, this yields a minimum mass of 2-3 M-circle dot for the compact companion, which implies that it may not necessarily be a black hole but a massive neutron- or main sequence star.Conclusions. The star LSV +22 25 has become famous for possibly having a very massive black hole companion. However, a closer look reveals that the star itself is a very intriguing object. Further investigations are necessary for complete characterization of this object.
Keywords: stars: abundances; stars: chemically peculiar; stars: early-type; pulsars: individual: LS V+22 25